A Preliminary Report: Radical Surgery and Stem Cell Transplantation for the Treatment of Patients With Pancreatic Cancer. Issue 4 (May 2017) - Omazic, Brigitta; Ayoglu, Burcu; Löhr, Matthias; Segersvärd, Ralf; Verbeke, Caroline; Magalhaes, Isabelle; Potacova, Zuzana; Mattsson, Jonas; Terman, Alexei; Ghazi, Sam; Albiin, Nils; Kartalis, Nikolaos; et al.
Abstract : We examined the immunologic effects of allogeneic hematopoietic stem cell transplantation (HSCT) in the treatment of pancreatic ductal adenocarcinoma, a deadly disease with a median survival of 24 months for resected tumors and a 5-year survival rate of 6%. After adjuvant chemotherapy, 2 patients with resected pancreatic ductal adenocarcinoma underwent HSCT with HLA-identical sibling donors. Comparable patients who underwent radical surgery, but did not have a donor, served as controls (n=6). Both patients developed humoral and cellular (ie, HLA-A*01:01-restricted) immune responses directed against 2 novel tumor-associated antigens (TAAs), INO80E and UCLH3 after HSCT. Both TAAs were highly expressed in the original tumor tissue suggesting that HSCT promoted a clinically relevant, long-lasting cellular immune response. In contrast to untreated controls, who succumbed to progressive disease, both patients are tumor-free 9 years after diagnosis. Radical surgery combined with HSCT may cure pancreatic adenocarcinoma and change the cellular immune repertoire capable of responding to clinically and biologically relevant TAAs. Abstract : Supplemental Digital Content is available in the text.